How Leader Narcissism Links to Team Voice Behavior: The Mediating Mechanisms of Leader Voice Solicitation and Team Voice Climate - Zhou, Rong; Yin, Wenjun; Sun, Lin (Frontiers in Psychology, 2021)
Drawing on the narcissism literature and social information processing theory, we theorized and examined a serial mediation model linking leader narcissism with team voice behavior through leader voice solicitation and team voice climate. We tested our hypotheses using data collected from a time-lagged and multisource survey of 223 frontline employees in 60 teams at a large manufacturing organization. The results indicated that leader narcissism had a negatively indirect effect on team voice climate via leader voice solicitation. Team voice climate positively predicted team voice behavior, and the indirect effects of leader narcissism via leader voice solicitation and team voice climate on team voice behavior were significantly negative. In this paper, we discuss the theoretical implications of our findings for both the narcissism literature and the voice literature, along with their practical implications.